Administration and Implementation of Educational Policy in Educational Institutions - Teskeaw, Warachaporn (MCU Haripunchai Review, 2026)
This study aims to examine the roles and competencies of school administrators in implementing educational policies within the context of Thailand’s education system, which faces challenges related to learning quality, educational inequality, and adaptation to the rapidly changing demands of the 21st century. The findings indicate that although national educational policies are clearly formulated, their implementation at the school level often lacks coherence and alignment with local contexts. School administrators play a crucial role as key mechanisms linking policy to practice through strategic planning, resource allocation, effective communication, and continuous monitoring and evaluation. Furthermore, contemporary school administration should move beyond traditional centralized command approaches toward holistic management that emphasizes stakeholder participation, including teachers, parents, communities, and related agencies, as well as evidence-based decision-making. Key recommendations include strengthening administrators’ strategic leadership, promoting stakeholder participation, emphasizing formative evaluation for continuous improvement, and designing measures to reduce educational inequality. The article concludes that the success of Thailand’s educational reform depends not only on sound policy design but also on effective school-level management capable of contextualizing policies and fostering sustainable educational quality improvement.